Aspects to consider when searching for persuasive strategies in tourism discourse - Zakharova, Ganna (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Tourism as a social phenomenon has attracted the attention of marketers throughout all stages of its development. Successful cooperation between tourism entities and customers is based on communication. The persuasive power of advertising language is very much experienced today. The same happens in relation to tourism marketing materials. In fact, in order to attract the attention of the viewers, the travel companies choose various signs to express their notion of the brand. Hence, there exist different approaches in tourism marketing to attract and convince potential tourists to book a tourism product. The present article elucidates and discusses important aspects in relation to the language of tourism and the ways of its analysis for detecting persuasive techniques that are used to allure potential tourists. In this regard, the speech impact on travel advertising is realized by convincing a potential customer of the need for service / product. When advertising a travel product, the advertiser influences the consumer, attracting various effective means to intensify his desire to purchase travel services (travel product). The paper reviews the elements of persuasive tourism marketing such as structured communication, storytelling, copywriting, neuromarketing; Cialdini’ (2001) persuasion techniques to influence people, namely, reciprocation, commitment and consistency, social proof, liking, authority, and scarcity. The article also highlights gender-targeting factors as important components in selecting an appropriate persuasive strategy when designing tourism promotional materials. The result section provides the real examples of deployment of the mentioned strategies in influencing the audience by the websites of “Karpaty” and “Solva” resorts. All these techniques form a theoretical framework for researches on persuasiveness and are worth attention as they play a main role in promotion of any kind. The data collection of this study will provide updated information in relation to rhetoric of tourism.